Positioning document of the Spanish Association of Paediatrics Group for the study of paediatric pain on the Registration of Pain as fifth vital sign - Moisés Leyva Carmona; Raquel Torres Luna; Lucia Ortiz San Román; Itziar Marsinyach Ros; Lucia Navarro Marchena; Ana Belén Mangudo Paredes; María Ceano-Vivas la Calle (Elsevier, 2019)
The Spanish Group for Children's Pain Study was created in 2017 in an aim to prevent, remove or reduce pain in neonates, infants, children and adolescents. Along with a diagnosis of pain, a paediatric patient may suffer from acute or chronic pain, neuropathic, nociceptive, or mixed pain, as well as pain from procedures, and post-surgical pain. Pain suffering is too often ignored and not diagnosed. As a result of this, pain prevention and pain treatment fails. Acute pain prevalence in scientific literature is estimated to be between 22% (procedures pain) and 77% (pain on patients in emergency departments and in hospital wards). Furthermore, up to 30% of children could suffer from chronic pain during their childhood. Among the barriers detected in pain management are: difficult assesment caused by a lack of unity in pain registry, difficulties due to the choice of an assessment pain scale (according to age and type of pain), and the absence of training in the management and interpretation of these pain scales. Additionally, in some health areas there is a high workload pressure and generally there are communication difficulties between professionals, and between them and families.From this AEP working group our clear positioning is expressed in the recommendation of the systematic assessment and recording of pain in all children treated in the health system, thus considering pain as the fifth constant to be determined after the other vital signs. Resumen: El Grupo Español para el Estudio del Dolor Pediátrico (GEEDP) se forma en 2017 con el objetivo de ayudar a reducir o eliminar el dolor de los neonatos, lactantes, niños y adolescentes. Ante un mismo diagnóstico de dolor, los pacientes pueden padecer dolores agudos, crónicos, por procedimientos, postoperatorio, nociceptivos, neuropáticos o mixtos. Sin una adecuada valoración clínica basada en la edad, la enfermedad de base y el tipo de dolor sospechado, este sufrimiento pasa desapercibido con demasiada frecuencia y como consecuencia es infratratado y poco prevenido. La prevalencia del dolor agudo en Pediatría es difícil de estimar y según la evidencia científica actual, podemos determinar que varía entre un 22% (dolor por procedimientos) y un 77% (dolor en los pacientes de urgencias y en las plantas de hospitalización); con relación al dolor crónico, hasta un 30% de los niños pueden padecerlo en algún momento de su vida. Entre las barreras detectadas en el diagnóstico de dolor se encuentran: la dificultad para su valoración por falta de unidad en su registro, existencia de diversas escalas de valoración (según edad y tipo de dolor) y por la ausencia de formación en manejo e interpretación de estas. A esto se puede sumar, en según qué ámbitos sanitarios, la elevada presión asistencial y las dificultades de comunicación entre profesionales y entre estos con las familias.Desde nuestro grupo de trabajo de la AEP deseamos manifestar nuestro claro posicionamiento en la recomendación de la valoración y registro del dolor de forma sistemática en todos los niños atendidos en el sistema sanitario, considerando así el dolor como la quinta constante a determinar después de las constantes vitales.